Detection of circulating natural antibodies to inflammatory cytokines in type-2 diabetes and clinical significance - Cai, Weiyi (J Inflamm (Lond), 2017)
BACKGROUND: Inflammatory cytokines have been demonstrated to be involved in developing insulin resistance and type-2 diabetes (T2D). Natural antibodies in the circulation have protective effects on common diseases in humans. The present study was thus designed to test the hypothesis that natural antibodies against inflammatory cytokines could be associated with T2D. METHODS: An enzyme-linked immunosorbent assay (ELISA) was developed in-house to detect plasma IgG against peptide antigens derived from interleukin 1α (IL1α), IL1β, IL6, IL8 and tumor necrosis factor-α (TNF-α) in 200 patients with T2D and 220 control subjects. RESULTS: Binary regression showed that compared with control subjects, T2D patients had a decreased level of plasma anti-IL6 IgG (adjusted r (2)=0.034, p=0.0001), anti-IL8 IgG (adjusted r (2)=0.021, p=0.002) and anti-TNF-α IgG (adjusted r (2)=0.017, p=0.003). Female patients mainly contributed to decreased levels of anti-IL6 IgG (adjusted r (2)=0.065, p=0.0008) and anti-IL8 IgG (adjusted r (2)=0.056, p=0.003), while male patients mainly contributed to decreased anti-TNF-α IgG levels (adjusted r (2)=0.024, p=0.005). ROC curve analysis revealed a sensitivity of 16.5% against specificity of 95.5% for anti-IL6 IgG assay and a sensitivity of 19.5% against specificity of 95.9% for anti-IL8 IgG assay. Glycated hemoglobin levels measured after 6-month glucose-lowering treatment appeared to be inversely correlated with plasma anti-IL1α IgG (r=-0.477, df=17, p=0.039) and anti-IL6 IgG (r=-0.519, df=17, p=0.023) although such correlation failed to survive the Bonferroni correction. CONCLUSIONS: Deficiency of natural IgG against inflammatory cytokines is likely to be a risk factor for T2D development and detection of such antibodies may be useful for personalized treatment of the disease. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12950-017-0171-6) contains supplementary material, which is available to authorized users.